2021
DOI: 10.1007/s10555-021-10010-6
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary perspective on the complex interactions between sleep, circadian, and metabolic disruption in cancer patients

Abstract: Sleep is a basic need that is frequently set aside in modern societies. This leads to profound but complex physiological maladaptations in the body commonly referred to as circadian disruption, which recently has been characterized as a carcinogenic factor and reason for poor treatment outcomes, shortened survival, and reduced quality of life in cancer patients. As sleep and circadian physiology in cancer patients spans several disciplines including nursing science, neurology, oncology, molecular biology and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 135 publications
1
17
0
Order By: Relevance
“…Furthermore, both the oncology infrastructure at the study site and differences in the motivation and workload among patient-recruiting nurses within different specialities may also play a role in determining the distribution of patients across different diagnoses in this study. Other studies looking at sleep disruption in cancer patients and correlating this to effects of treatments have similar cohort sizes to that of the present study (Innominato et al, 2012;Jensen et al, 2021), but are focusing on more defined patient populations. Innominato et al (2012), for example, studied circadian disruption using Actigraph accelerometers worn on the wrist for 3 days and found that sleep disruption in 77 patients with metastatic colorectal cancer undergoing medical treatment with 5-FU, Oxaliplatin and/or Leucovorin had significantly shortened survival compared to those with non-disrupted sleep (Innominato et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, both the oncology infrastructure at the study site and differences in the motivation and workload among patient-recruiting nurses within different specialities may also play a role in determining the distribution of patients across different diagnoses in this study. Other studies looking at sleep disruption in cancer patients and correlating this to effects of treatments have similar cohort sizes to that of the present study (Innominato et al, 2012;Jensen et al, 2021), but are focusing on more defined patient populations. Innominato et al (2012), for example, studied circadian disruption using Actigraph accelerometers worn on the wrist for 3 days and found that sleep disruption in 77 patients with metastatic colorectal cancer undergoing medical treatment with 5-FU, Oxaliplatin and/or Leucovorin had significantly shortened survival compared to those with non-disrupted sleep (Innominato et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
“…While this is a somewhat crude assessment of sleep disruption, these guidelines represent the first attempt to include this important issue in routine cancer care. Within clinical research, however, numerous questionnaires and other instruments have been developed to investigate sleep disruption in cancer patients [recently reviewed by Jensen et al (2021) ]. The most commonly used is the extensive 19-item Pittsburgh Sleep Quality Index ( Divani et al, 2022 ), which however is time-consuming to both fill and analyze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP9 (matrix metallopeptidase 9) is involved in the proteolytic modification of ECM proteins, which affects neuronal plasticity and the synaptic properties of neurons ( Hayashi et al, 2013 ). In addition, melatonin has also a regulatory effect on the MMP9 pathway and ECM remodeling ( Jensen et al, 2021 ). These results further confirmed a link between the immune-inflammatory response and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Circadian disruption could also account for digestive complaints, 101 sleep troubles, 102 and altered metabolism. 103 Thus, the accurate evaluation of circadian function through remote monitoring of cancer patients 83 could represent a biomarker of physiological and behavioral alteration, 75 a surrogate of symptom burden and of subjective complaints, 100 , 104 , 105 as well as a potential novel target of intervention, both pharmacological and behavioral. 79 …”
Section: Circadian Phenotypingmentioning
confidence: 99%